Islamic finance in Australia: the potential problems and prospects - Faruq Ahmad, Abu Umar; Osmani, Noor Mohammad; Karim, Mohd Fazlul (2010)
Islamic finance began in the 1960s, accelerated rapidly during the 1970s and has grown significantly in the 1990s as a result of banking deregulation in the 1980s. Although Islamic finance emerged in Australia in 1990s in response to the growing demand of 350,000 of its Muslim population through establishment of the Muslim Community Cooperative Australia Limited, it did not grow substantially due to an enormous problems faced by Islamic finance industry. The underlying problem in this regard is Australia’s legislative and regulatory framework. In order to thrash out these problems and examine the potentials of Islamic finance in this continent we did not attempt to evaluate the economic efficiency and profitability or otherwise, of Islamic finance in Australia. Also, the approach for the study is not supplemented by any empirical work. The method employed in this study is a mixture of direct observation from legal and regulatory perspectives and authors’ personal experience, curiosity and association with this industry. However, Shari`ah remains the only theoretical basis of the study. Through examining the above the paper seeks to argue that since the principles Islamic finance differ from its conventional counterparts a separate legal framework should be established to facilitate its growth and development in the Australian financial market.